The relationship of burnout with job satisfaction and suicide ideation among anesthesiologists. Issue 2 (2015) - Özkan, Süreyya; Karaman, Emine Uzlaş; Öztürk, Nalan; Ahun, Filiz Akın; Selmi, Nazan Has
No abstract available